MODERN VIEWS ON THE EPIDEMIOLOGY, ETIOLOGY, AND CLINICAL PRESENTATION OF LYME DISEASE - Chemych, M.; Chemych, O.; Seemann, O.; Klymenko, N.; Svitaylo, V.; Saienko, O.; Delikatna, T. (Eastern Ukrainian Medical Journal, 2025)
Relevance. Lyme disease (LD) is the most prevalent tick-borne infectious disease and poses a significant health risk in countries in the northern hemisphere. Unlike other zoonoses, LD causes significant medical, social, and economic damage due to its high incidence and the severity of its clinical course. Complications can lead to disability and necessitate long-term dispensary observation and costly examinations. Objective: To find out the current scientific views on the peculiarities of epidemiology, clinical course of Lyme disease, and mechanisms leading to multiorgan damage. Materials and methods. We analyzed scientific articles and studies on Lyme disease, covered in the databases PubMed, Medline, Cochrane Library, Center for Public Health of the Ministry of Health of Ukraine, Karger, RKI, Onlinelibrary, CDC, Ecdc. Particular attention was paid to studies that investigated the etiology, prevalence, and clinical features of LD. The articles published from 2016 to 2025 were analyzed using the methods of systematic literature review, comparative analysis of clinical outcomes, and meta-analysis to ensure the relevance and accuracy of the conclusions. Results. Surveillance of LD in Europe is carried out in only 25 out of 52 countries (48.1%) and is hampered by differences in national standards and reporting agreements. The introduction of standardized case definitions in surveillance systems in Europe will be important to establish the true incidence of LD and to track its burden in relation to future interventions, including vaccination. To this end, a review of national surveillance strategies is urgently needed, with wider adoption of standardized case definitions to optimize their utility before a vaccine is available. The development of new methods of disease risk control and prediction for better targeted control interventions requires an understanding of pathogen and disease course, so it is desirable to create maps of the distribution of Ixodes ticks and the extent of their infection. In order to confirm the diagnosis of LD in patients with peripheral or central nervous system disorders, it is recommended to detect antibodies in the blood serum rather than PCR, since PCR should be performed using cerebrospinal fluid. When diagnosing heart rhythm disorders in endemic areas, patients should be examined to exclude or confirm the disease as a cause of carditis. In patients with LD and high fever or characteristic laboratory abnormalities, the possibility of coinfection with A. phagocytophilum and/or B. microti in endemic areas should be excluded and other infectious agents should be considered.